Morbidity patterns and long-term outcomes of central lymph node dissection in thyroid cancer patients - Khalid Atallah; Shadi Awny; Khaled Abdelwahab; Ahmed Abdallah; Islam H Metwally; Omar Hamdy; Mohammed Zuhdy; Ahmed Fareed (Scientific Reports)
Abstract Central lymph node metastasis (CLNM) is observed in 20-90% of patients with differentiated thyroid cancer (DTC). Central lymph node dissection (CLND) is associated with a higher incidence of complications, including hypocalcemia and an increased risk of recurrent laryngeal nerve injury. This study aimed to characterize and analyze the morbidity of CLND precisely. This is a retrospective cohort study that included patients who were diagnosed with thyroid cancer and underwent total thyroidectomy and CLND at a tertiary cancer center from January 2012 to December 2023. Among 420 patients, intraoperative complications were observed in 47 patients (11.2%). The commonest was recurrent laryngeal nerve palsy, which occurred in 16 patients. Stridor was detected immediately after extubating five patients. The commonest postoperative complication was hypocalcemia, which occurred in 69 patients (16.4% of patients), 21 patients (5%) required hospital re-admission, and most of them were temporary (79.4%). CLND may lead to morbidity in 1 to 2 of every 10 patients. Better diagnostic tools and predictive models are mandatory to identify the central compartment disease burden. Moreover, more advanced surgical techniques are needed to spare the patients the potential complications.